SISTEM INFORMASI GEOGRAFIS PELAPORAN MASYARAKAT (SIGMA) BERBASIS FOTO GEOTAG - Mardani, Ary (Jurusan Informatika Universitas Tanjungpura, 2014)
The problems that occur in thesocietysuch as bad infrastructure and public welfarecause information about the location of the problembecomes very important to be known by thegovernment. Society Reporting GeographicInformation Systems (SIGMA) is an application thatprovides information based on the geographicalposition of a photograph. With the SIGMA, thesociety could help the government to collectinformation about the location of the problem withuploading photos via the web and the androidapplication so that the government can monitor thedistribution of the location of the problem, planningand taking countermeasures quickly and accurately,especially for areas far from the government’sattention. This application utilizes the phone'scamera featuresthat has a direct synergy with theGPS feature to provide information about the objectand the condition known as geotagging. Photos thenuploaded via a web application, or using androidapplication which can be downloaded from thewebsite. Through GPS metadata contained in thepicture, SIGMA will get the coordinates for thelocation of the photo then displayed it on the map.The results show that the web and the androidapplication can upload photos that have coordinateinformation. The test results of a questionnaire usingLikert's method Summated Rating (LSR) earned atotal score of 2369 which showed that respondentsare very positive and successful application.